Rheticus: Dynamic and continuous geoinformation service for critical infrastructure and environmental monitoring (GEOmedia, 2017)
Using free & open images captured by the Copernicus Sentinel satellites, the Rheticus cloudbased platform delivers industry-focused geoinformation services, in form of dynamic maps, reports, geo-analytics and alerts for professionals, private companies and Public Authorities, involved in engineering, utilities, energy, mining, land planning, environment and land monitoring.Subscribed users can receive contiuous information and analytics on the stability of infrastructures (dams, roads, railways, pipelines, etc.), slope stability and subsidence, the quality of coastal marine waters, forest fires and anthropic changes of the territory.